Mutation and Transmission Profiles of Second-Line Drug Resistance in Clinical Isolates of Drug-Resistant Mycobacterium tuberculosis From Hebei Province, China - Li, Qianlin; Gao, Huixia; Zhang, Zhi; Tian, Yueyang; Liu, Tengfei; Wang, Yuling; Lu, Jianhua; Liu, Yuzhen; Dai, Erhei (Frontiers in Microbiology, 2019)
The emergence of drug-resistant tuberculosis (TB) is involved in ineffective treatment of TB, especially multidrug resistant/extensively resistant TB(MDR/XDR-TB), leading to acquired resistance and transmission of drug-resistant strains. Second-line drugs (SLD), including both ﬂuoroquinolones and injectable drugs, were commonly proved to be the effective drugs for treatment of drug-resistant TB. The purpose of this study was to investigate the prevalence of SLD-resistant strains and its specific mutations in drug-resistant Mycobacterium tuberculosis clinical isolates, and to acknowledge the transmission pattern of SLD resistance strains in Hebei. The genes gyrA, gyrB, rrs, eis promoter and tlyA of 257 drug-resistant clinical isolates were sequenced to identify the mutations for mutations that could be responsible for resisting fluoroquinolones and second-line injectable drugs. Each isolate was genotyped by Spoligotyping and 15-loci MIRU-VNTR. Our results indicated that 48.2% isolates were resistant to at least one of five SLD. Of them, 37.7% isolates were resistant to fluoroquinolones and 24.5% isolates were resistant to second-line injectable drugs. Mutations in genes gyrA, gyrB, rrs, eis promoter and tlyA were detected in 73 (75.3%), 7 (7.2%), 24 (38.1%), 5 (7.9%) and 3 (4.8%) isolates, respectively. The most prevalent mutations were the D94G (23.7%) in gyrA gene and the A1401G (33.3%) in rrs gene. A combination of gyrA, rrs and eis promoter can act as a valuable predicator for predicting XDR phenotype. These findings highlight the development of rapid diagnosis are the effective manners for the control of SLD-TB or XDR-TB.